Reconstructing Health Communication in the Digital Intelligence Era: A Review of the 8th International Conference on Medicine, Humanity, and Media - Gao, Yujing; Jiang, Yueliang (The Journal of Medicine, Humanity and Media, 2025)
The 8th International Conference on "Medicine, Humanity, and Media", organized by the School of Journalism and Communication at Peking University, took place from July 6 to July 11, 2025. The conference centred on the theme "Reconstructing Health Communication in the Digital Intelligence Era." Scholars and experts from over 60 universities and research institutions convened to discuss the rapidly evolving field of health communication in response to advances in artificial intelligence (AI) and digital media technologies. Notably, the integration of doctoral forum marked an innovative aspect of this year's symposium. Additional activities, including summer course lectures, poster presentations, workshop, university colloquiums, and high-table dialogues, fostered extensive academic exchanges.